La reception du Livre d’Amos par les peres. Proposition Methodologique - Charpin-Ploix, Marie Lucie (Vox Patrum, 2018)
Is the method of tracking scriptural references to determine the influence of a biblical book on the Fathers of the Church sufficient? Or, would it be more appropriate to expand our methodological resources by taking the convergence of different types of elements into account ? This article seeks to demonstrate the complementary nature of these methods through the example of the reception of the Book of Amos by four Fathers of the Church. The list of quotations by Justin Martyr, Ireanaeus, and Origen is used to perceive how they appeal to and interpret the Book of Amos, as well as the particular status they grant it. In addition to this initial method, a semantic and stylistic analysis of Basil of Caesarea’s Homily VIII reveals supplementary forms of the reception of Amos and thus indicates the important influence of the prophet on this Father and Doctor of the Church.